What is the number six million, thirty thousand, expressed in scientific notation? 6.03 × 10^6
6.3 × 10^5
6.3 × 10^6
6.03 × 10^4

Answers

Answer 1
The answer is B. 6.3 * 10^6
6.3 * 10^6 = 6,300,000
Hope this helps!
Answer 2
One million is 10 x 10 x 10 x 10 x 10 x 10, or 10^6. 6,030,000 would be 6.3 x that.

So, your answer is: B) 6.3 x 10^6

Related Questions

Which number would it be if rounded to the nearest foot

7191.51


A. 7191 FT

OR

B. 7192 FT

Answers

7191.51 ft rounds to 7192 ft.  Since the number 7191 is followed by a 5, it rounds up.

Stephanie rdes her bike 2 miles to the post office, and then another 50 yards to the train station. How many yards long was her trip?

Answers

There are 1,760 yards in a mile.

Multiply 1,760 by 2 = 3,520

Add 50 to 3,520 = 3,570

Stephanie's trip was 3,570 yards long.

Let d(t) =6t^2 be the distance function, find the average velocity from (4, 4.1)

Answers

this would be 6*(4.1)^2 - 6*4^2 = 4.86
average v = 4.86 / 0.1 =  48.6 

Which box plot represents the data?

135, 149, 156, 112, 134, 141, 154, 116, 134, 156

Answers

To get the box plot we begin by arranging the data in ascending order:
135, 149, 156, 112, 134, 141, 154, 116, 134, 156
rearranging we get:
112,116, 134, 134, 135, 141, 149, 154, 156, 156
then:
Lower value=112
Q1=134
Median=(135+141)/2=138
Q3=154
Largest value=156

The second figure is the correct figure.

The box plot that represents the data is option B.

What is a box plot?

A box plot is known to be a method that is employed to demonstrate the locality and skewness of numerical data. This is carried out graphically and done through the quartiles of the given numerical data.

Rearranging the given data, we have:

112,116, 134, 134, 135, 141, 149, 154, 156, 156

The minimum value after rearranging = 112.

First Quartile, Q1 = 134.

Second Quartile, Q2 or Median = 135+141/2 = 276/2 = 138

Third Quartile, Q3 = 154

Largest figure = 156

The answer is the second figure.

Learn more about box plot on https://brainly.com/question/14277132

Using the discriminant, how many real number solutions does this equation have? 3x^2 – 2 = 5x

Answers

The discriminant of this equation is 49. The solutions for this equation are x=2 and x=-[tex] \frac{1}{3} [/tex]
I hope that helps.

Please help!!!


Use DeMoivre's theorem to evaluate the expression

[sqrt 3( cos 5pi/3 + i sin 5pi/3)]^4 ? write the answer in rectangular form


a. 9sqrt3/2 + 9/2 i

b. 9sqrt3/2 - 9/2 i

c. -9/2 - 9sqrt3/2 i

d. -9/2 + 9sqrt3/2 i

Answers

DeMoivre's theorem

if z = a ( cos θ + i sin θ)
∴ z^n = a^n ( cos nθ + i sin nθ)

For the given complex number ⇒⇒⇒ [ √3 ( cos 5π/3 + i sin 5π/3 ) ]⁴
[ √3 ( cos 5π/3 + i sin 5π/3 ) ]⁴ = (√3)⁴  ( cos 4*5π/3 + i sin 4*5π/3 )
= 9 ( cos 20π/3 + i sin 20π/3 )
= 9 ( cos 2π/3 + i sin 2π/3 )
 = 9 ( -1/2 + i √3 /2 )
= -9/2 + 9√3 /2 i

note: 20π/3 = 2π/3 + 6π = 2π/3 + 3 *2π = 2π/3

∴ The correct answer is option d
   d. -9/2 + 9sqrt3/2 i










Answer:

Option d - [tex]\sqrt3(\cos (\frac{5\pi}{3})+i\sin(\frac{5\pi}{3}))^4=-\frac{9}{2}+\frac{9\sqrt3}{2}i[/tex]      

Step-by-step explanation:

Given : [tex]\sqrt3(\cos (\frac{5\pi}{3})+i\sin(\frac{5\pi}{3}))^4[/tex]

To find : Use DeMoivre's theorem to evaluate the expression?

Solution :

DeMoivre's theorem state that, for complex number

If [tex]z = r(\cos\theta+ i\sin \theta)[/tex] then [tex]z^n = r^n(\cos n\theta+ i\sin n\theta)[/tex]

We have given,

[tex]\sqrt3(\cos (\frac{5\pi}{3})+i\sin(\frac{5\pi}{3}))^4[/tex]

On comparing [tex]r=\sqrt3[/tex] and n=4

Applying DeMoivre's theorem,

[tex]=(\sqrt3)^4(\cos 4(\frac{5\pi}{3})+i\sin4(\frac{5\pi}{3}))[/tex]

[tex]=9(\cos (\frac{20\pi}{3})+i\sin(\frac{20\pi}{3}))[/tex]

[tex]=9(\cos (6\pi+\frac{2\pi}{3})+i\sin(6\pi+\frac{2\pi}{3}))[/tex]

[tex]=9(\cos (\frac{2\pi}{3})+i\sin(\frac{2\pi}{3}))[/tex]

We know, the value of

[tex]\cos (\frac{2\pi}{3})=-\frac{1}{2},\sin (\frac{2\pi}{3})=\frac{\sqrt3}{2}[/tex]

[tex]=9(-\frac{1}{2}+i\frac{\sqrt3}{2})[/tex]

[tex]=-\frac{9}{2}+i\frac{9\sqrt3}{2}[/tex]    

Therefore, Option d is correct.

[tex]\sqrt3(\cos (\frac{5\pi}{3})+i\sin(\frac{5\pi}{3}))^4=-\frac{9}{2}+\frac{9\sqrt3}{2}i[/tex]      

Rewrite 0.85 as a fraction in lowest terms.

Answers

17/20 because it would be 85/100 and 5 goes into 85 17 times and 5 goes into 100 20 times.
simply and shortly put, we "use as many zeros at the bottom as there are decimals and lose the dot", what the dickens does that mean?

well, 0.85 has two decimals, so we use two zeros,00, at the bottom of the fraction and lose the dot, let's do so,

[tex]\bf 0.\underline{85}\implies \cfrac{085}{1\underline{00}}\implies \cfrac{85}{100}\implies \stackrel{simplified}{\cfrac{17}{20}}[/tex]

sabendo que x2 + y2=74 e que xy=35, calcule valor de (x - y2)2

Answers

To solve this problem you must apply the proccedure shown below:

 1. You have the following information given in the problem above:

 - x²+y²=74
 xy=35

 2. Therefore, you have that (x-y)² is:

 =(x-y)²
 =x²-2xy+y²
 =(x²+y²)-2xy

 3. When you substitute the values given in the problem, you obtain:

 =74-2(35)
 =74-70
 =4

 4. Therefore, as you can see, the correct answer is: 4

 

PLZ HELP ME!! You will earn 15 POINTS and BRAINLIEST!!!!
What is the average rate of change of the function over the interval x = 0 to x = 6? f(x)=2x−1
                                                   ____
                                                   3x+5

Answers

[tex]\bf slope = m = \cfrac{rise}{run} \implies \cfrac{ f(x_2) - f(x_1)}{ x_2 - x_1}\impliedby \begin{array}{llll} average~rate\\ of~change \end{array}\\\\ -------------------------------\\\\ f(x)=\cfrac{2x-1}{3x+5} \qquad \begin{cases} x_1=0\\ x_2=6 \end{cases}\implies \cfrac{f(6)-f(0)}{6-0}[/tex]

[tex]\bf \cfrac{\left[ \frac{2(6)-1}{3(6)+5} \right]~~-~~\left[ \frac{2(0)-1}{3(0)+5} \right]}{6}\implies \cfrac{\left[ \frac{11}{23}\right]~~-~~\left[-\frac{1}{5} \right]}{6} \\\\\\ \cfrac{\frac{11}{23}+\frac{1}{5}}{6}\implies \cfrac{\quad \frac{78}{115}\quad }{\frac{6}{1}}\implies \cfrac{78}{115}\cdot \cfrac{1}{6}\implies \cfrac{13}{115}[/tex]

students have 40 minuets to complete 50 questions on the aspire ___ test


A) math


B) reading


C) english


D) writing

Answers

I believe the answer to this is C. English.

Answer:

english C)  

Step-by-step explanation:

Find the first six terms of the sequence. a1 = -3, an = 2 ● an-1

Answers

The first term of the sequence is -3.

According to the formula each next term will be obtained by multiplying the previous term by 2.

So, next terms will be:

Second term = 2 x First Term = 2 x (-3) = - 6

Third term = 2 x (-6) = -12

Fourth term = -24

Fifth term = -48

Sixth term = -96

So, the sequence will be:

-3, -6, -12, -24, -48, -96 ...

The height of a tree in feet over x years is modeled by the function f(x). f(x)=301+29e−0.5x which statements are true about the growth of the tree? select each correct answer. the tree's maximum height is limited to 30 ft. the tree is initially 2 ft tall. between the 5th and 7th years, the tree grows approximately 7 ft. after growing 15 ft, the tree's rate of growth decreases.

Answers

Final answer:

The tree's maximum height is not limited to 30 ft but approaches 301 ft. Initially, the tree is 30 ft tall, not 2 ft. To verify the growth between the 5th and 7th years, one must calculate f(5) and f(7). The rate of growth indeed decreases over time.

Explanation:

When analyzing the function f(x) = 301 + 29e^{-0.5x} to understand the growth pattern of a tree, it is apparent that some statements about the tree's growth can be identified as true or false.

The tree's maximum height is not limited to 30 ft; instead, the model suggests that the height approaches 301 ft as x increases indefinitely, because the exponential term decreases towards zero.The tree is initially 30 ft tall, not 2 ft tall, since f(0) = 301 + 29 × 1 = 330 ft.Between the 5th and 7th years, the growth can be calculated using f(5) and f(7) to determine if it grows approximately 7 ft during that period.After growing 15 ft, the rate of growth would decrease since the exponential function's growth rate decreases as x increases.

Which transformation is a rotation?

Answers

maybe the one where the are facing eachother?

Answer:

the answer is c.

Step-by-step explanation:


Cam rode her bike 5 times as far as Dante did. Dante rode 187 meters farther than Michael did. Cam rode 15.25 Kilometers. How many meters did Michael ride? Explain how you know you got your answer

Answers

Let Dante's distant be x, Cam's will be 5x
Given that Cam rode 15.25 km
then
5x=15.25
x=3.05 km

thus Dante rod 3.05 km
but
1 km=1000m
thus
3.05 km=3050 m
But Dante rod 187 m more than Michael, the distance Michael will ride then  will be:
3050-187
=2863 m



It was found that Michael rode 2863 meters.

To find out how many meters Michael rode, we first need to establish the relationship between the distances Cam, Dante, and Michael rode. According to the problem, Cam rode 5 times as far as Dante did. If Cam rode 15.25 kilometers, we first convert this to meters by multiplying by 1000 (since there are 1000 meters in a kilometer):

15.25 km × 1000 = 15250 meters.

Now that we know Cam rode 15250 meters and that this is 5 times the distance Dante rode, we can find Dante’s distance:

15250 meters / 5 = 3050 meters.

Dante rode 3050 meters, which is 187 meters farther than Michael did. To find the distance Michael rode, we subtract 187 meters from Dante’s distance:

3050 meters - 187 meters = 2863 meters.

Therefore, Michael rode 2863 meters.

i need help!!!!!!!!!!!!!!?!!!

Answers

In Quadrant I, sin(sin^-1(x)) = x.

The appropriate choice is
  B. [tex]\dfrac{\sqrt{3}}{2}[/tex]

A card is drawn randomly from a standard deck of cards. you win $10 if the card is a spade or an ace. what is the probability that you will win the game?

Answers

The probability of winning is 4/13.

These two events are not mutually exclusive; this means they can happen at the same time.  For two events that are not mutually exclusive,

P(A or B) = P(A) + P(B) - P(A and B)

This gives us 
P(spades or Ace) = P(spades) + P(Ace) - P(spades and Ace)

There are 13 spades out of 52 cards.
There are 4 aces out of 52 cards.
There is 1 card that is a spade and an ace out of 52 cards.

13/52 + 4/52 - 1/52 = 16/52 = 4/13

Factor each polynomial. Check your answer by distributing. 2x^2+5x+2

Answers

The answer of the factored polynomial is
(X+2)(2x+1)

The function f(x)=35+15x represents the amount of money, in dollars, mr. lewis earns for working x hours. how much money does mr. lewis earn for working 25 hours?

Answers

410. 

You can get this by plugging in the 25 for x in the above equation. 
Final answer:

By substituting x with 25 in the equation f(x)=35+15x, we find out that Mr. Lewis would earn $410 for working 25 hours.

Explanation:

The function provided is f(x)=35+15x, which represents the amount of money Mr. Lewis earns for working x hours. In the case of Mr. Lewis working for 25 hours, we substitute the value of x with 25 in the equation to calculate his earnings. Therefore, f(25)=35+15(25)=35+375=$410. Hence, Mr. Lewis would earn $410 for working 25 hours.

Learn more about Linear Functions here:

https://brainly.com/question/31353350

#SPJ3

Find the value of the lesser root of x^2-6x+8=0

Answers

x² - 6x +8= 0,          

[tex]x= \frac{-b+/- \sqrt{b^{2}-4ac} }{2a} a=1, b=-6, c=8 [/tex]

[tex]x= \frac{6+/- \sqrt{36-4*1*8} }{2*1} x=(6+/- \sqrt{36-32} )/2 x=(6+/-2)/2 x_{1} =4, x_{2}=2[/tex]


Answer:

The value of lesser root is:

                         x=2

Step-by-step explanation:

We are given  a quadratic equation in terms of variable " x " as:

[tex]x^2-6x+8=0[/tex]

We know that for any quadratic equation of the type:

              [tex]ax^2+bx+c=0[/tex]

The roots of x are calculated as:

[tex]x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]

Here we have:

      a=1 , b=-6 and c=8

Hence, on solving for roots:

[tex]x=\dfrac{-(-6)\pm \sqrt{(-6)^2-4\times 1\times 8}}{2\times 1}\\\\\\x=\dfrac{6\pm \sqrt{36-32}}{2}\\\\\\x=\dfrac{6\pm \sqrt{4}}{2}\\\\\\x=\dfrac{6\pm 2}{2}[/tex]

Hence, we have:

[tex]x=\dfrac{6+2}{2}\ or\ x=\dfrac{6-2}{2}\\\\x=\dfrac{8}{2}\ or\ x=\dfrac{4}{2}\\\\\\x=4\ or\ x=2[/tex]

Hence, the value of lesser root is:

                             x=2

Stan's cookie recipe makes 242424 cookies and calls for exactly 384384384 sprinkles. He is wondering how many sprinkles (p)(p)left parenthesis, p, right parenthesis he will need to make 606060 cookies. He assumes each cookie will have the same number of sprinkles. How many sprinkles does Stan need to make 606060 cookies?

Answers

If these numbers are correct:

For every 242,424 cookies he needs 384,384,384 sprinkles. So how many sprinkles does he need for 606,060 cookies?

242,424/384,384,384 = 606,060/x

384,384,384 * 606,060 = 242,424 * x

232,959,999,767,040 = 242,424 * x

960,960,960 = x

To find the number of sprinkles needed for 60 cookies, determine the number of sprinkles per cookie by dividing 384 by 24, which is 16. Then multiply 16 by 60 to get 960 sprinkles.

The question asks us to calculate the number of sprinkles (p) needed for 60 cookies when a recipe for 24 cookies calls for 384 sprinkles.

To solve this, we start by finding the number of sprinkles per cookie:

Divide the total number of sprinkles (384) by the number of cookies in the recipe (24).Multiply the result by the number of cookies we want to make (60).

Therefore:

384 sprinkles ÷ 24 cookies = 16 sprinkles per cookie 16 sprinkles per cookie × 60 cookies = 960 sprinkles for 60 cookies

Stan would need 960 sprinkles to make 60 cookies.

24 inches is 250% of what length

Answers

24 inches is 250% of 9.6 inches, if that's not one of the options google "250% of (insert one of the options here)
The answer is:  " 9.6 inches " .
________________________________________________________
Explanation:
________________________________________________________

24 = 250/100 * x  ;

24 = 2.5 x ; 

↔  2.5 x = 24 ; 

2.5 x / 2.5 = 24/ 2.5 ; 

x = 9.6 ; 

The answer is:  " 9.6 inches " .
_________________________________________________________

Factor this trinomial completely.

10x2 + 7x – 12

A. (2x + 3)(5x – 4)
B. (x + 4)(10x – 3)
C. (x + 3)(10x – 4)
D. (2x + 4)(5x – 3)

Answers

First you want to write 7x as a sum or difference: 15x-8x
Now, the expression would look like this: 10x^2+15x-8x-12
Next, factor out the 5x and -4 from the expression: 5x(2x+3)-4(2x+3)
Now, factor out the 2x+3 from the expression and you have your answer:
(2x+3)(5x-4)
Final answer:

The trinomial "10[tex]x^2[/tex] + 7x - 12" is factored by finding two numbers that multiply to -120 and add up to 7, which are 15 and -8. Split the middle term, group, and factor by grouping to get (2x + 3)(5x - 4), which is option A.

Explanation:

To factor the trinomial "10x2 + 7x − 12" completely, you want to find two binomials that, when multiplied together, will give you the original trinomial. To do this, you will need two numbers that multiply to give you the product of the coefficient of the x2 term (which is 10) and the constant term (which is −12), which equals −120, and also add up to the coefficient of the x term (which is 7).

The two numbers that meet these criteria are 15 and −8, since (15)(−8) = −120 and 15 + (−8) = 7. Next, split the middle term of the trinomial using these two numbers:

10x2 + 15x − 8x − 12

Now, group the terms:

(10x2 + 15x) − (8x + 12)

Factor out the greatest common factor from each group:

5x(2x + 3) − 4(2x + 3)

Finally, factor out the common binomial factor:

(2x + 3)(5x − 4)

Therefore, the correct factorization of the trinomial 10x2 + 7x − 12 is (2x + 3)(5x − 4), which corresponds to option A.

In circle H, HJ¯¯¯¯¯ is a radius and JK¯¯¯¯¯ is a tangent segment. Which statement must be true?

A) HJ=JK
B) ∠HJK is an obtuse angle.
C) HJ=HK
D) ∠HJK is a right angle.

Answers

ITS RIGHT ANGLE YALL I FOUND IT
The Answer is D.

D) ∠HJK is a right angle.

The center of a circle is at (2, -5) and it's radius is 12. What is the equation of the circle?

A.) (x+2)^2 + (y-5)^2 =24
B.) (x-2)^2 + (y+5)^2 = 24
C.) (x+2)^2 + (y-2)^2 = 144
D.) (x-2)^2 + (y+5)^2 = 144

Answers

The equation for a circle is (x-h)^2 +(y-k)^2=r^2
You just have to plug in your coordinates h is the x and k is the y.
The r is radius squared.
so, (x-2)^2+(y-(-5)^2=144
You have to be careful of those tricky negative values. When you distribute the y-(-5) it turns into y+5. 
So your answer is D.

Answer:

The answer is D

Step-by-step explanation:

It is D

A bus covered the 400-km distance between points a and b at a certain speed. on the way back the bus traveled at the same speed for 2 hours and then increased the speed by 10 km/hour until it reached a, thus spending 20 fewer minutes on the return trip. how long did the return trip take?

Answers

Let the speed going to B be x, the time taken be t and distance is 400 km
xt=400, 
On the way back, the 2x+(x+10)(t-7/3), where it was total time minus 2 hours already driven minus 1/3 of hour, the 20 minutes.
2x+xt-(7/3)x+10t-70/3=400
2x+400-(7/3)x+10t-70/3=400
thus
-(1/3)x+4000/x=70/3
multiplying through by x we get:
-(1/3)x^2-(70/3)x+4000=0
x^2+70x-12000=0
x=(1/2)(-70+/-sqrt52900)
x=80 kmp
thus:
it took 5 hours to make the first trip 
on way back 2 hours at 80 kph which means he traveled for 160 km at this speed
2 h 40 min at 90 k/h=90*8/3=240 km

The speed going to B is x, the time t and the distance, 400 km.

xt=400, x kph and t in hours

on the way back, the 2x+(x+10)(t-7/3), where it was total time minus 2 hours already driven minus 1/3 of an hour, the 20 minutes.

2x+xt-(7/3)x+10t-70/3=400

2x+400-(7/3)x+10t-70/3=400, 400 cancels, t=400/x

-(1/3)x+4000/x=70/3

multiply by x

-(1/3)x^2-(70/3)x+4000=0

x^2+70x-12000=0

x=(1/2)(-70+/- sqrt 52900); sqrt term=230

x=80 kph

took 5 hours to go there

on way back 2 hours at 80 kph=160 km

2h40m at 90kph=90*8/3=240 km

They add to 400 km.

The return trip took 4h40m

Write a single algebraic rule for the series of transformations: a reflection about the x-axis, a rotation of 90 degrees clockwise, and a translation of 4 units right and 2 units down.

Answers

To a point (x,y), a reflection about the x-axis first does this
                           (x,y) → (x,-y)
A rotation of 90 degrees clockwise
                           (x,-y) → (-y,-x)
Translating 4 units right and 2 units down
                           (x,-y) → (-y + 4,-x - 2)
Therefore your answer is (x,y) → (-y + 4,-x - 2)

Simplify i to the power 41

Answers

[tex]\bf \textit{recall that }i^4=1\\\\ -------------------------------\\\\ i^{41}\implies i^{40+1}\implies i^{40}\cdot i^1\implies i^{4\cdot 10}\cdot i\implies (i^4)^{10}\cdot i\implies 1\cdot i\implies i[/tex]

Answer:

It should be just "i"

What is the surface area of the prism? Include steps.

Answers

First things first. This is a rectangular prism, so it's faces are all rectangles.

Area of a rectangle: Area = Length x Height

- Rectangular Prism Dimensions:

Length: 3m
Width: 4m
Height: 2m


To calculate the surface area of a rectangular prism we first need to realize that he has 3 pairs of equal rectangles.

- The first pair (Photo 1):

Two rectangles with the same measure, so we can say that the area of this pair is: (L x H) x (L x H) or 2 x (L x H).

-> Area (Pair 1) = 2 x (3 x 2) = 2 x 6 = 12m^2

But if we will do the same thing to 3 different pairs, we can describe that:

- Total Surface Area (At):

At = 2 x (L x H) + 2 x (L x H) + 2 x (L x H)

-> At = 2 x ((L x H) + (L x H) + (L x H))

So now, just put the values inside de formula,

- Pair 1: Length = 3m ; Height = 2m

- Pair 2: Length = 4m ; Height = 2m

- Pair 3: Length = 4m ; Height = 3m

*I know that this pair doesn't have a "real Height" but this doesn't change anything when solving, you can consider the 4m as height and the 3m as length or vice versa, the order of the factors doesn't change the product.

-> At = 2 x ((3 x 2) + (4 x 2) + (4 x 3))
-> At = 2 x (6 + 8 + 12)
-> At = 2 x (26)

-> At = 52 m^2

If you shift the linear parent function, f(x)=x, down 7 units what is the equation of the new function

Answers

To solve this problem you must apply the proccedure shown below:

 1- You have that following parent function (the most basic function of the linear functions) given in the problem above:

 f(x)=x

 2- When you graph this parent function, you obtain the graph shown in the figure attached.

 3- If you shift the linear parent function 7 units down, you have the following new function:

 f(x)=x-7

 4- The graph of the new function is shown in the second figure attached.

 The answer is: f(x)=x-7

f(x)=x-7 is indeed the correct answer.just got it right

Write an equation and solve: Twice a number, increased by 3 is 7.

Answers

the equation is 2x+3=7
2x +3=7
      -3  -3
2x=4
divide both sides by 2
x=2
the answer is 2
Other Questions
Verify that the divergence theorem is true for the vector field f on the regione. give the flux. f(x, y, z) = 4xi + xyj + 4xzk, e is the cube bounded by the planes x = 0, x = 2, y = 0, y = 2, z = 0, and z = 2. Calculate the total cost of the order: Veggiburger with cola and soup, sales tax 4%, tip 15.Veggiburger: $3.25Cola: $1.50Soup: $2.25A $8.33B $7.28C $7.00D $5.50 What happens in meiosis during the telophase ||A. The mitotic spindle forms. B. A total of four daughter cells form. C. Two diploid cells at produced.D. DNA doubles to produce sister chromatids. How did the laws of coverture affect women? The neurotransmitter _____, which helps to control the preciseness of the signal sent from one neuron to another, decreases with aging Which statement best explains why comparing Lincoln to a ship captain is an appropriate comparison? Figure abcdf is a dilation or figure abcdf by a scale factor of 1/2. The dilation is centered at (-4,-1)Which statement is true? While handling preserved biological specimens what safety equipment should you be using ? A- fire blanketB - thermal glovesC- eye wash station D - latex gloves After seizing control of japan's government, japanese military leaders: The gap between the rich and poor in Mexico is largely a result of the _____.Mexican governments system of governmentsubsistence farming practices favored by ejidosfact that the majority of Mexicans live in urban areashacienda system established in the past A sample of a compound contains 32.0g C and 8.0g H. Its molar mass is 30.0/mol. What is the compounds molecular formula? do not go gentle into that good night figurative language explaination Which best describes Homer?A: He was a Trojan who took part in the events of the illiad.B: He is the poet who told that illiad.C: He is the main character of the illiad.D: He was the first person to write down the illiad.The answer is, B.(He is the poet who told that illiad.) Sally is making sun tea. Every hour, the concentration of the tea doubles. If it takes 6 hours for the tea to be ready, how long would it take for the tea to reach half of the final concentration (in hours)? Which of these is an example of a random sample?A.The manager of a baseball team asks his team members about their views on the previous game they played.B.For a survey on air travel, 100 people are chosen randomly from five different airports.C.Five players from a basketball team are chosen for a game.D.Three members of a band are chosen for a concert. France has recently banned people from covering their faces in public, which was widely understood to target muslim women from wearing full-face veils. this indicates that the ______ cleavage is still salient in france. ________ refers to a genetically influenced weight range for an individual that is maintained by biological mechanisms that regulate food intake, fat reserves, and metabolism. Lucy created a design with different shapes. Stars made up 1/4 of all the shapes in the design. Eight ninths of the stars are red. What fraction of all the shapes are red stars? Red cabbage juice can be used as an acid-base indicator. When a solution is highly acidic, the juice turns red. As the acidity decreases and the solution becomes basic, the color changes from red to violet to green to yellow. Red cabbage juice is used as an indicator of some common household products. Which product will turn yellow when cabbage juice is added? A)coffee B)ammonia C)vinegar D)bottled water In general as the similarity of the structure between solvent and solute increases the solubility does what